Ultrasound guided dextrose prolotherapy for chronic medial collateral ligament injuries in young footballers - Rosdi, Muhammad Harith; Kamaruddin, Nabil Fikri (IIUM Press, 2026)
Dextrose prolotherapy (DPT) is increasingly recognized for its regenerative potential in managing ligamentous injuries. However, evidence supporting its use in medial collateral ligament (MCL) injuries among young athletes remains scarce. This case series describes four adolescent footballers (aged 14–16 years) with chronic medial knee pain unresponsive to rehabilitation. Three athletes with isolated MCL injuries achieved complete pain resolution within 4 –6 weeks following ultrasound-guided 12.5% dextrose injections, combined with knee bracing and structured rehabilitation. They successfully returned to full training after passing functional assessments, with no reinjury at 3- and 6- month follow-ups. Conversely, the fourth athlete, with concomitant MCL, anterior cruciate ligament, and meniscal injuries, experienced only partial pain relief and sustained reinjury after premature return to play, ultimately requiring surgical intervention. These findings suggest that DPT may accelerate recovery in isolated chronic MCL injuries but has limited benefit in multiligament knee injuries.